Effect of Intellectual Intelligence and Emotional Intelligence on Employee Performance - Inna Nisawati Mardiani; Fahmi AL Hanafi (JURNAL PELITA ILMU, 2020)
One of the company's success depends on its employees. To be able to increase company productivity, it is necessary to know the effect of intellectual intelligence and emotional intelligence on employee performance. This research was conducted on 59 of 141 employees at PT. Flexi Components Indonesia. Emotional intelligence and intellectual intelligence are independent variables and employee performance as the dependent variable. This study uses survey methods, samples and questionnaires as the main data collection tools. The validity and reliability of the questions were tested for each variable. Then, emotional intelligence and intellectual intelligence variables were regressed on employee performance. The results of this study indicate that the intellectual intelligence variable has an effect on employee performance, and the emotional intelligence variable has a significant effect on the employee performance of PT. Flexi Components Indonesia.